Miron Białoszewski: alienacja i utopia. O neoawangardowych kontekstach poezji Białoszewskiego - Świeściak, Alina (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-ansi-language: EN-US; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-US">The article deals with the problem of avant-garde character of the poetry by Miron Białoszewski in the context of alienation and dealienatively understood utopias. This is the way the language is understood here, being, on the one hand, an anonymous “language without an end”, and, on the other hand – an extremely privatized code, as the transgressive neo-avant-garde ideas inscribed in this kind of writing: experiencing life as art and the recognition of art as an event from life, and thus a myth of art as an experience parallely private and intimate and aesthetically-social. Consequently, the relationships with neoavant- garde in the Białoszewski’s poetry are treated as an expression of the modernist artistic crises, and, at the same time, as a tool helping to overcome them.